The Influence Of Organizational Culture And Leadership Style On Performance Through Motivation As An Intervening Variable At PT Indonesia Chemi-Con: Pengaruh Budaya Organisasi dan Gaya Kepemimpinan terhadap Kinerja melalui Motivasi sebagai Variabel Intervensi di PT Indonesia Chemi-Con - Mat Mursalin; Sri Mulyani; Arif Hidayat (OGZ Research & Publishing, 2026)
Abstract: This study aims to analyse the influence of organisational culture and leadership style on employee performance mediated by work motivation among employees of PT Indonesia Chemi Con. This study uses a quantitative approach with a survey method. Data was collected by distributing questionnaires to employees of PT Indonesia Chemi Con as research respondents. The data analysis technique used was Structural Equation Modelling (SEM) with a Partial Least Squares (PLS) approach. The results of the study indicate that organisational culture has a positive and significant effect on employee performance. In addition, leadership style also has a positive and significant effect on employee performance. Furthermore, the results of the study prove that organisational culture and leadership style have a positive and significant effect on work motivation. Work motivation is also proven to have a positive and significant effect on employee performance. The test results show that work motivation acts as a mediating variable that strengthens the influence of organizational culture on employee performance. In addition, work motivation has also been proven to mediate the influence of leadership style on employee performance. Thus, it can be concluded that the improvement in employee performance at PT Chemi Con Indonesia is not only directly influenced by organizational culture and leadership style, but also indirectly through increased work motivation Keywords: Organizational Culture, Leadership Style, Work Motivation, Employee Performance